Tendency of dynamic vasoactive and inotropic medications data as a robust predictor of mortality in patients with septic shock: An analysis of the MIMIC-IV database - Ning, Yi-Le; Sun, Ce; Xu, Xiang-Hui; Li, Li; Ke, Yan-Ji; Mai, Ye; Lin, Xin-Feng; Yang, Zhong-Qi; Xian, Shao-Xiang; Chen, Wei-Tao (Frontiers in Cardiovascular Medicine, 2023)
Background: Septic shock patients fundamentally require delicate vasoactive and inotropic agent administration, which could be quantitatively and objectively evaluated by the vasoactive–inotropic score (VIS); however, whether the dynamic trends of high-time-resolution VIS alter the clinical outcomes remains unclear. Thus, this study proposes the term Reduction Rate of VIS (VRR) to mediate the tendency of dynamic VIS, to explore the association of VRR and mortality for patients with septic shock. Methods: We applied dynamic and static VIS data to predict ICU mortality by two models: the long short-term memory (LSTM) deep learning model, and the extreme gradient boosting (XGBoost), respectively. The specific target cohort was extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database by the sophisticated structured query language (SQL). Enrolled patients were divided into four groups by VRR value: ≥50%, 0 50%, -50% 0, and < -50%. Statistical approaches included pairwise propensity score matching (PSM), Cox proportional hazards regression, and two doubly robust estimation models to ensure the robustness of the results. The primary and secondary outcomes were ICU mortality and in-hospital mortality, respectively. Results: VVR simplifies the dosing trends of vasoactive and inotropic agents represented by dynamic VIS data while requiring fewer data. In total, 8887 septic shock patients were included. Compared with the VRR ≥50% group, the 0 50%, -50% 0, and < -50% groups had significantly higher ICU mortality [hazard ratio (HR) 1.32, 95% confidence interval (CI) 1.17-1.50, p < 0.001; HR 1.79, 95% CI 1.44-2.22, p < 0.001; HR 2.07, 95% CI 1.61-2.66, p < 0.001, respectively] and in-hospital mortality [HR 1.43, 95% CI 1.28-1.60, p < 0.001; HR 1.75, 95% CI 1.45-2.11, p < 0.001; HR 2.00, 95% CI 1.61-2.49, p < 0.001, respectively]. Similar findings were observed in two doubly robust estimation models. Conclusion: The trends of dynamic VIS in ICU might help intensivists to stratify the prognosis of adult patients with septic shock. A lower decline of VIS was remarkably associated with higher ICU and in-hospital mortality among septic shock patients receiving vasoactive–inotropic therapy for more than 24h.